Improving Teacher Professional Competence: The Principal’s Leadership Role at SDN Kota Baru IV - Hikmawati, Syifa Dwi; Yohamintin, Yohamintin (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research aims to determine the leadership role of school principals in improving teachers' professional competence at SDN Kota Baru IV. Using a qualitative case study approach, this study involved key stakeholders, including the principal and teachers from various grade levels. The subjects used in this research were the Principal and Class VI A Teachers, Class II B Teachers, Class C- D Teachers, Class III B Teachers, Class VI C Teachers, Class VI B Teachers. Data collection techniques were carried out by observation, interviews, and accompanied by documentation. The methods used in data analysis were data collection, data reduction, data presentation, and conclusion drawing. The triangulations used were source triangulation and method triangulation. Results reveal that the principal effectively embodies multiple leadership roles educator, manager, administrator, leader, and motivator to foster teacher competence. For instance, as an educator, the principal cultivates a positive learning culture and encourages professional development through workshops and seminars. As a manager, the principal ensures systematic planning and optimal utilization of resources. Furthermore, as a motivator, the principal inspires teachers to embrace innovation and continuous improvement. This research underscores the pivotal influence of leadership in achieving educational excellence, emphasizing the integration of strategic management and professional development to overcome challenges and enhance teacher performance.